Vehicle Trajectory Prediction Considering Multi-feature Independent Encoding Based on Graph Neural Network - Su, Xiao; Wang, Xiaolan; Li, Haonan; Xu, Xin; Wang, Yansong (Recent Patents on Mechanical Engineering, 2024)
Background: Today, self-driving cars are already on the roads. However, driving safety remains a huge challenge. Trajectory prediction of traffic targets is one of the important tasks of an autonomous driving environment perception system, and its output trajectory can provide necessary information for decision control and path planning. Although there are many patents and articles related to trajectory prediction, the accuracy of trajectory prediction still needs to be improved. Objective: This paper aimed to propose a novel scheme that considers multi-feature independent encoding trajectory prediction (MFIE). Methods: MFIE is an independently coded trajectory prediction algorithm that consists of a spacetime interaction module and trajectory prediction module, and considers speed characteristics and road characteristics. In the spatiotemporal interaction module, an undirected and weightless static traffic graph is used to represent the interaction between vehicles, and multiple graph convolution blocks are used to perform data mining on the historical information of target vehicles, capture temporal features, and process spatial interaction features. In the trajectory prediction module, three long short-term memory (LSTM) encoders are used to encode the trajectory feature, motion feature, and road constraint feature independently. The three hidden features are spliced into a tensor, and the LSTM decoder is used to predict the future trajectory. Results: On datasets, such as Apollo and NGSIM, the proposed method has shown lower prediction error than traditional model-driven and data-driven methods, and predicted more target vehicles at the same time. It can provide a basis for vehicle path planning on highways and urban roads, and it is of great significance to the safety of autonomous driving. Conclusion: This paper has proposed a multi-feature independent encoders’ trajectory prediction data-driven algorithm, and the effectiveness of the algorithm is verified with a public dataset. The trajectory prediction algorithm considering multi-feature independent encoders provides some reference value for decision planning.
Keywords: long short-term memory